Knowledge and attitudes of mexican dentists regarding COVID-19 = Conocimiento y actitudes de dentistas mexicanos sobrela COVID-19 - Bermeo Escalona, Josué Roberto; Cerda Cristerna, Bernardino Isaac (2023)
Dentists have a high risk of contracting COVID-19, they needed to be aware of the major challenge that represents the dental practice and COVID-19. Accordingly, this study aimed: 1) to investigate the knowledge of dentists regarding COVID-19, 2) to investigate the attitudes of dentists concerning the use of personal protective equipment and, 3) to investigate the attitudes of dentists on stopping their dental practices in the framework of a contingency plan for the COVID-19 outbreak. An online cross-sectional survey was applied to dentists (n=822). Dentists in Mexico answered the survey, which was administered before the contingency plan for the COVID-19 outbreak. Results were analyzed with descriptive statistics and with a Chi-square test (P≤0.05). Of the respondents, 99% of dentists indicated knowing what COVID-19 is, knowing most, but not all, of its signs and symptoms and knowing its mode of transmission. The 89% of dentists indicated that they always used personal protective equipment. But they did not use always wear face masks, protective eyewear, face shields, disposable gowns, and caps. Dentists were aware of the risk of performing dental procedures during the COVID-19 outbreak. The 90% of dentists indicated that they would treat only patients requiring emergency treatment, and 10% indicated that they would not treat any patients. The dentists had limited knowledge about the COVID-19 disease. They did not use personal protective equipment consistently, and they indicated that they might continue working during the COVID-19 outbreak.
Durante la pandemia por COVID-19, los dentistas han tenido un alto riesgo de contraer COVID-19. Los dentistas mexicanos tuvieron la necesidad de enfrentarse a la COVID-19 en la práctica dental con un posible conocimiento limitado sobre la enfermedad. De acuerdo con esa problemática, los objetivos de este estudio fueron: 1) investigar el conocimiento de los dentistas sobre la COVID-19, 2) investigar las actitudes de los dentistas sobre el uso de equipo de protección personal, 3) investigar las actitudes de los dentistas para detener la práctica laboral frente a la pandemia. Una encuesta fue aplicada a dentistas mexicanos en el inicio de la contingencia por COVID-19 (n=822). Se analizaron los resultados de con una prueba de Chi cuadrada (P≤0.05). El 99% de los participantes conocieron qué es la COVID-19, pero no todos los signos y síntomas de la enfermedad ni los modos de transmisión. El 89% de los dentistas indicaron que siempre usan equipo de protección personal. Pero no usan siempre careta, lentes de protección, cubreboca, guantes deshechables y gorro. Los participantes tenían conocimiento del riesgo de contraer COVID-19. El 90% indicó que sólo atenderían urgencias dentales y el resto indicó que no atendería pacientes. Los dentistas tuvieron un conocimiento limitado sobre la COVID-19. No usaron equipo de protección personal de forma consistente. Además indicaron que estarían dispuestos a seguir trabajando durante la pandemia.
En revista Odóvtos, vol. 25, no.1 (enero-abril 2023)
Descripción basada en el contenido visto el 13 de diciembre, 2024
También disponible en formato HTML y EPUB